Bread from stones: Post-mining land use change from phosphate mining to farmland. Issue 2 (April 2017) - Howieson, John; Calmy, Hervé; Ballard, Neil; Skinner, Peter; WO'Hara, Graham; Skinner, Lorri; Ruthrof, Katinka X.; Swift, Rebecca; Ballard, Val; St Hardy, Giles E.; McHenry, Mark P.
Abstract: Modern mining jurisdictions commonly require a mine-site to be restored to its original land-use when mining is completed. However, the conversion of disused mine sites for agricultural purposes (rather than restoration to an original condition) is an innovative strategy as food security in many regions becomes critical. Selected mine-sites on Christmas Island were converted to an agricultural land use as the mining company withdrew from mineral extraction in the aim to achieve employment, economic, and socio-economic benefits for the isolated island population (pop. ∼2000). The Australian Government co-funded this research with a mining company (Phosphate Resources Limited) to assess the science required to introduce commercial agriculture to the island. This paper describes land-use change methods and results, including pre-commercial trials of selected broadacre crops, rotational cropping using legumes, high value crops, and a microbial prospecting program to determine capability of indigenous bacteria. This research demonstrates a range of successful methods have enabled a new post-mining land-use to productive farmland from an apatite (phosphate) minesite. We have outlined where productive use of post-mining lands is both desirable and has proven to be particularly challenging, but which can lead to a productive and commercially viable opportunity in both advanced and emerging economies.